Antidiabetic Activity of Ethyl Acetate Compounds from Gayam (Inocarpus fagiferus): In Silico and In Vivo Studies - Ifaya, Mus; Ridwan, Bai Athur; Laugi, Putri Salsabila; Utami, Apriliani Putri; Abdurrahman, Syawal (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Diabetes mellitus is characterized by high blood sugar levels. Though many drugs are available, blood glucose control is still challenging to achieve due to decreased beta cell function and side effects of long-term use. Gayam tree bark (Inocarpus fagiferus) has the potential to inhibit digestive enzymes, although the molecular mechanism of its antidiabetic effect has not been ascertained. This study aims to determine the activity of compounds from ethyl acetate extract as antidiabetics, tested in silico and in vivo. The study used molecular docking and in vivo activity analysis. LC-MS analysis was used to determine the content of compounds in the ethyl acetate fraction of gayam bark. Through molecular interaction prediction and ADME-Toxicology, compounds in gayam bark showed antidiabetic activity. In the molecular docking interaction study, the Cochliophilin A compound had a lower binding energy than acarbose on the α-amylase receptor: -9.76 kcal/mol and -8.95 kcal/mol. The ADME-Tox model predicted good skin permeability, absorption, and distribution for Cochliophilin A. The ethyl acetate extract showed antidiabetic activity in lowering blood sugar levels in rats on day 14, respectively by 74% (IV), 72% (V), and 74% (VI). Collectively, compounds in gayam bark are useful in treating diabetes.